Patterns of amalgamation in cross-border mergers and acquisitions: Evidence from Malaysian multinational firms - Jedin, Mohd. Haniff; Md Saad, Norsafinas (2012)
Many studies in cross-border mergers and acquisitions (M&A) involve variety of management disciplines such as finance, accounting, business and human resource. However, an in-depth study in patterns and tendencies of cross-border M&A integration particularly in Malaysia is neglected and nearly no study has ever discussed Malaysian M&A integration trends particularly after the South East Asia financial turmoil 1997-1999. Thus, this study attempts to explore this phenomenon especially to identify the background of Malaysian industries that involved in cross-border M&A.Interestingly, this paper also reveals the integration trends involved when engaging in cross-border M&A.A survey was used using Thomson One Banker as the main database which covered completed Malaysian M&A cases. Results show that engineering, software and telecommunication industries are among the leading industries engaged in cross-border M&A.In terms of nationality of the acquired firms, Indonesia, Thailand and Singapore are among favourites to Malaysian acquirers.In fact, the study exposed a positive development of cross-border M&A which demonstrate higher success compared to failures.